A self-roughened and biodegradable superhydrophobic coating with UV shielding, solar-induced self-healing and versatile oil-water separation ability - Dong, Xiuli (2020)
Traditional superhydrophobic coatings prepared from non-degradable materials tend to do harm to the environment throughout the fabrication process as well as after being discarded. Great efforts have been devoted to exploring more environmentally friendly approaches and materials to settle this problem. Here we report an eco-friendly strategy based on aqueous systems to construct superhydrophobic coatings on various fabrics. Fabrics were first coated with polydopamine (PDA) and then modified with the stearic acid emulsion to introduce the desired surface morphology and energy. The as-prepared fabrics achieved robust superhydrophobicity with a contact angle (CA) about 162.0° and sliding angle (SA) about 7.8°. Moreover, due to the UV-absorbing and the photo-thermal conversion ability of PDA, the modified fabrics exhibited excellent UV shielding and solar-induced self-healing properties. The as-prepared fabrics also possessed high efficiency oil–water separation properties. Without the usage of harmful organic solvents and the addition of micro/nano-particles, this biodegradable superhydrophobic fabric exhibited a clear advantage of being environmentally friendly over conventional coatings. Furthermore, the facile and low-cost fabrication process makes its large-scale production easy.